2018
DOI: 10.3390/s18113773
|View full text |Cite
|
Sign up to set email alerts
|

A Flexible 12-Lead/Holter Device with Compression Capabilities for Low-Bandwidth Mobile-ECG Telemedicine Applications

Abstract: In recent years, a number of proposals for electrocardiogram (ECG) monitoring based on mobile systems have been delivered. We propose here an STM32F-microcontroller-based ECG mobile system providing both long-term (several weeks) Holter monitoring and 12-lead ECG recording, according to the clinical standard requirements for these kinds of recordings, which in addition can yield further digital compression at stages close to the acquisition. The system can be especially useful in rural areas of developing coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
(22 reference statements)
1
7
0
Order By: Relevance
“…Compared with similar devices presented in the literature, our prototype has a lower power consumption than other Wi-Fi based systems [34,35] which is similar to results achieved by other systems using Bluetooth [13,[31][32][33] and ISM wireless communication [19,29].…”
Section: Discussionsupporting
confidence: 80%
“…Compared with similar devices presented in the literature, our prototype has a lower power consumption than other Wi-Fi based systems [34,35] which is similar to results achieved by other systems using Bluetooth [13,[31][32][33] and ISM wireless communication [19,29].…”
Section: Discussionsupporting
confidence: 80%
“…Without adequate attention to the barriers, there is a significant risk that telehealth will exacerbate health inequities 47 . A serious problem lies in the inadequate telehealth infrastructure 48 . According to Morgan et al, 23 the success of the telemedicine component of the clinic is due in large part to the excellent infrastructure support provided by the Telehealth Saskatchewan Network.…”
Section: Discussionmentioning
confidence: 99%
“…47 A serious problem lies in the inadequate telehealth infrastructure. 48 According to Morgan et al, 23 the success of the telemedicine component of the clinic is due in large part to the excellent infrastructure support provided by the Telehealth Saskatchewan Network. A person who had to travel more than 100 km for a telehealth appointment was almost 9 times more likely to interrupt an appointment than the person who had to travel <50 km, and the risk of interrupting an appointment tended to increase as the distance saved by using telehealth decreased.…”
Section: Discussionmentioning
confidence: 99%
“…The other three papers in this classification presented clinical cases of remote monitoring using mobile devices. Pineda-Lopz et al [ 32 ] reported on a long-term Holter monitoring and 12-lead ECG recording system using mobile phones in Spain. They concluded that a 32-bit mobile microcontroller ECG system can be especially useful in rural areas of developing countries, where the lack of specialized medical personnel justifies the introduction of telecardiology services.…”
Section: Discussionmentioning
confidence: 99%